Apakah Mengakes Instagram Bisa Meningkatkan Pemahaman Informasi Tentang Al-Qur’an? - Ayu Kurnia; Luqman (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
The study aims to determine the effect of the intensity of accessing the Instagram da'wah account @Quranreview on the understanding of Al-Qur'an information among followers of the Instagram da'wah account @Quranreview and the magnitude of the influence. This study uses quantitative with simple linear regression analysis. Statistical calculations were carried out using SPSS 26 software. The sample in this study was 100 respondents from followers of the @Quranreview account. The conclusion of the study shows that there is an effect of the intensity of accessing the Instagram da'wah account @Quranreview on the understanding of Al-Qur'an Information among its followers. This is based on the results of a simple linear regression test obtained by the equation Y = 17.807 + 0.697X. From the regression equation that the variable of understanding the Al-Qur'an is 17.807 and the variable of access intensity is 0.697 states that for every 1% increase in intensity value, the value of understanding Al-Qur'an Information increases by 0.697. Therefore, there is an effect of understanding the Al-Qur'an on followers when accessing the Instagram da'wah account @Quranreview. The large influence obtained in the intensity of accessing the Instagram account of dakwah @Quranreview on the understanding of Al-Qur'an Information can be seen from the determination coefficient test, where the R-square value of 0.569 shows that the contribution of the variable intensity of accessing the Instagram account of dakwah @Quranreview and understanding of the Al-Qur'an is 56.9% while the remaining 43.1% is a contribution from other factors that were not examined in this study.